Comparison Of The Effectiveness Of Cooperative Learning Model Of Tps Type And Nht Type Based On Independent Learning Students At Makassar - Abdul Hadi (Journal of Educational Science and Technology (EST), 2017)
The study is an experiment research with pretest and postets design, which aims at examming (1) the effectiveness of cooperative lerning model of TPS type; (2) the effectiveness of cooperative lerning model of NHT type; (3) and the comparison of the the effectiveness of cooperative lerning model of TPS type and NHT type based on independent learning of students. The result of the study reveal that (1) the impelementation of cooperative learning model of TPS type is effective when impelemented in class VIII at MTsN 2 Makassar of plane space geometry; (2) the impelementation of cooperative learning model of NHT type is effective when impelemented in class VIII at MTsN 2 Makassar of plane space geometry; (3) there are differences of the effectiveness of cooperative learning model of TPS type and NHT type based on independent learning of students on plane space geometry in class VIII at MTsN 2 Makassar which in high category; (4) there is not difference of the effectiveness of cooperative learning model of TPS type and NHT type based in independent learning of students on plane space geometry in class VIII at MTsN 2 Makassar which in not high category.